Impact of ocean resolution on coupled air‐sea fluxes and large‐scale climate. Issue 19 (13th October 2016) - Roberts, Malcolm J.; Hewitt, Helene T.; Hyder, Pat; Ferreira, David; Josey, Simon A.; Mizielinski, Matthew; Shelly, Ann
Abstract: Air‐sea fluxes are a crucial component in the energetics of the global climate system. The largest air‐sea fluxes occur in regions of high sea surface temperature variability, such as ocean boundary, frontal currents and eddies. In this paper we explore the importance of ocean model resolution to resolve air‐sea flux relationships in these areas. We examine the sea surface temperature‐wind stress relationship in high‐pass filtered observations and two versions of the Met Office climate model with eddy‐permitting and eddy‐resolving ocean resolutions. Eddy‐resolving resolution shows marginal improvement in the relationship over eddy‐permitting resolution. However, by focussing on the North Atlantic we show that the eddy‐resolving model has significant enhancement of latent heat loss over the North Atlantic Current region, a long‐standing model bias. While eddy‐resolving resolution does not change the air‐sea flux relationship at small scale, the impact on the mean state has important implications for the reliability of future climate projections. Key Points: Demonstrate that eddy‐permitting is sufficient to capture observed temporal relationship between SST, wind stress over boundary currents Eddy‐resolving resolution improves mean state of fluxes and leads to changes in large‐scale modeled heat transport Benefits of high ocean resolution improving mean state may be more important than direct influence of changes to air‐sea interactions